PREPARATION OF HETEROGENEOUS ION-EXCHANGE MEMBRANE BY PORE FILLING METHOD - Septina Sirait, Anastasia
Ion-exchange membrane (IEM) is an important part of several electro-membrane processes used for water treatment and energy storage. For these processes to run effectively, an ion-exchange membrane with good separation characteristics, such as high conductivity, high permselectivity, and good chemical and mechanical stability, is required. Based on their structure, ion exchange membranes are divided into two, namely homogeneous and heterogeneous membranes. Homogeneous membranes have good eletrochemical properties, but the fabrication process is difficult. Meanwhile, heterogeneous membranes are easier to fabricate and have good mechanical strength. However, heterogeneous membranes have insufficient electrochemical properties due to non-uniform charge distribution. With the right preparation method, heterogeneous membranes are expected to have superior characteristics. Heterogeneous structure ion exchange membrane was fabricated from polypropylene by streching technique and pore filling with sulfonated polysulfone. Experiments were conducted by varying the stretching ratio and temperature to test its effect on the membrane charasteristic. The result showed that the addition of sulfonated polysulfone affected the membrane characteristic, characterized by a decrease in water contact angle and an increase in water absorption. The results showed that the stretching ratio variation in the range 25% to 150% and the stretching temperature variation in the range of 80 °C to 120 °C will increase the water absoprtion, conductivity, and ion exchange capacity. The highest water absorption value was 0.145 g H2O/g membrane. The highest conductivity value was 0.680 mS/cm. The highest ion exchange capacity values was 1.98 meq/mL.